Three new ground dweller Mesabolivar González-Sponga, 1998 (Araneae: Pholcidae) from Blumenau, Santa Catarina, Brazil - Machado, Éwerton O.; Brescovit, Antonio D.; Francisco, Rafael C. (Zootaxa, 2007)
Three new ground dwelling pholcid species of the genus Mesabolivar from Blumenau, Santa Catarina, Brazil, are described: M. huberi n. sp., M. rudilapsi n. sp., and M. embapua n. sp.